REPRODUKSI GENDER MELALUI TRANSMISI TEKS AGAMA - Elizabeth, Misbah Zulfa (Jurnal THEOLOGIA, 2012)
The sustainability and cultural change, including gender, was associated with the delivery of value between generations. The existence of well-established interpretation of the text, which does not allow a new interpretation of the text, which is delivered to religious community make gender values remained relatively unchanged, even continuously reproduced. In this case, the transmitter of religious value, the preachers, seen in the Muslim community as the respectable and credible persons. Therefore, the doctrine they convey tend to be trusted and obeyed, without any possibility of other interpretations. The delivery model of one-direction model of messages delivery with lack of dialogue and participation of the audiences, no chance to new interpretations are another causes that led the concept of gender relatively unchanged